2004
DOI: 10.1677/jme.0.0320237
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia is modified by the presence of the polymorphism present in the exon 1 variant at the SR-BI gene locus

Abstract: It has recently been reported that carriers of the less common allele at the scavenger receptor class B type I (SR-BI) exon 1 polymorphism are more susceptible to the presence of saturated fatty acid in the diet because of a greater increase in LDL cholesterol. Our aim was to determine if this polymorphism could also influence postprandial lipoprotein metabolism, because the SR-BI has been described as a possible mediator in the intestinal absorption of triacylglycerols. Forty-seven normolipidemic volunteers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Taken together, these observations strongly suggest that postprandial HDL metabolism is intimately related to SR-BI activity. In this context, it is relevant that SR-BI has been previously shown to modulate postprandial triglyceride response through its action on intravascular chylomicron metabolism ( 38,39 ) and more recently through its action on intestinal cholesterol absorption and TRL secretion ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these observations strongly suggest that postprandial HDL metabolism is intimately related to SR-BI activity. In this context, it is relevant that SR-BI has been previously shown to modulate postprandial triglyceride response through its action on intravascular chylomicron metabolism ( 38,39 ) and more recently through its action on intestinal cholesterol absorption and TRL secretion ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that SR-BI's role in the reverse cholesterol transport pathway is particularly important for cholesterol metabolism in rodents, it is not clear whether this is true in humans. However, several recent studies have reported genetic polymorphisms that implicate SR-BI as a significant player in human HDL cholesterol metabolism as well (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Although the magnitude of the genetic effect on variation in the postprandial lipid response is unknown, each of these genes seems to have a small, yet measurable, effect on postprandial lipid metabolism. Interestingly, polymorphisms in some of the PPARa-mediated genes, such as LPL, APOC3, APOA5, and SCARB1, modify the postprandial TG response (35)(36)(37)(38)(39). In this study, we report that PPARa is involved in the homeostasis of lipids in the fasted state as well as during the acute postprandial response to dietary fat.…”
Section: Discussionmentioning
confidence: 62%